ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BELAJAR DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Efendi, Rahmi Maldini; Afandi, Muslim; Subhan, Mhd. (JURNAL KAJIAN ISLAM MODERN, 2025)
Learning is the core of the entire process of educational activities that take place. The quality of the learning process greatly determines the quality of the overall educational outcome, including in the formation of the character and personality of students. This study aims to analyze the factors that influence the learning process of students in the perspective of Islamic educational psychology. This study departs from the understanding that the learning process does not only involve cognitive aspects, but also includes affective and spiritual dimensions, which are the main focus in Islamic education. This study uses a literature review method with primary sources from books on Islamic educational psychology. Secondary sources include various literature such as scientific journals and relevant books that can support the depth and sharpness of the research analysis. The results show that the factors that influence learning can generally be grouped into two, namely internal and external factors. Internal factors include physiological, psychological conditions (intelligence, attention, interest, talent, motivation, attitude, maturity and readiness), and fatigue. Meanwhile, external factors include family, school and community environments. In the perspective of Islamic educational psychology, these factors need to be understood holistically because they are related to the formation of students' morals, spirituality, and Islamic personality. This research contributes to designing learning strategies that are more meaningful, integrative, and contextual in accordance with Islamic values, as well as strengthening the role of teachers, parents, and society in creating a conducive learning environment for the formation of the ideal human being (insan kamil).